The Black Side of Resilience - Sofia Nobre; Florencio Vicente Castro (INFAD, 2016)
Resilient individuals are described as strong personalities experiencing adversity with no signs of stress traumatic symptoms and still achieving success. However we can apply the metaphor of materials to human beings. With resistant materials as concrete we can notice the danger of rupture, at the first time the force was unbearable by its fissure signs. But not with resilient materials as an elastic, it recovers its initial and previous harmonious state with no symptoms of vulnerability, even when submitted to great force of extension, nevertheless not dramatically strongly, because one single event of extension or extending it over and over again with no pause between events could imply rupture without notice, so we understand it’s not just due its flexible and adaptable nature or because it didn’t “feel” the force, but because at that moment the charge was bearable and it had sufficient time to recover. Understanding the importance of the factor time to recover, as well as the danger of sudden rupture for resilience, the point of this work is to find a pattern of the biomarkers associated with allosteric load and loss of resilience to prevent sudden rupture.